2021
DOI: 10.1186/s12936-021-03796-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malaria diagnostic refresher training programme on competencies and skills in malaria diagnosis among medical laboratory professionals: evidence from Ghana 2015–2019

Abstract: Background The quality of malaria test results is crucial for optimal patient treatment and care. The Ghana Health Service is successfully shifting from presumptive clinical diagnosis and treatment of malaria to the Test, Treat and Track (T3) initiative. In line with the initiative, the National Malaria Control Programme (NMCP) set out to improve the capacity of medical laboratory professionals in Ghana through a five-day Malaria Diagnostic Refresher Training (MDRT) to build competencies and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Both RDTs used during the survey are WHO prequalified and, therefore, should meet requirements for safety and quality ([ 17 ] and https://extranet.who.int/pqweb/vitro-diagnostics/vitro-diagnostics-lists ). However, the performance of malaria RDT is dependent on several factors in addition to parasite densities [ 18 ] such as reduced community level transmission intensities [ 19 ]; operator skill [ 20 , 21 ], correct transport and storage conditions [ 22 ] and a strong product lot quality monitoring program [ 21 ]. In spite of high performance of PfLDH detection RDTs reported by others [ 12 , 23 25 ], the lower sensitivity and specificity of LDH detection RDT reported in this study, 69% and 72% sensitivity against PCR and multiplex assay, respectively and 38% and 36% specificity against PCR multiplex, respectively, could be partly driven by samples with low parasitaemia below the detection threshold of the PfLDH RDT.…”
Section: Discussionmentioning
confidence: 99%
“…Both RDTs used during the survey are WHO prequalified and, therefore, should meet requirements for safety and quality ([ 17 ] and https://extranet.who.int/pqweb/vitro-diagnostics/vitro-diagnostics-lists ). However, the performance of malaria RDT is dependent on several factors in addition to parasite densities [ 18 ] such as reduced community level transmission intensities [ 19 ]; operator skill [ 20 , 21 ], correct transport and storage conditions [ 22 ] and a strong product lot quality monitoring program [ 21 ]. In spite of high performance of PfLDH detection RDTs reported by others [ 12 , 23 25 ], the lower sensitivity and specificity of LDH detection RDT reported in this study, 69% and 72% sensitivity against PCR and multiplex assay, respectively and 38% and 36% specificity against PCR multiplex, respectively, could be partly driven by samples with low parasitaemia below the detection threshold of the PfLDH RDT.…”
Section: Discussionmentioning
confidence: 99%
“…• Guideline for community private drug peddlers and retailers. Tetteh et al 2021 Ansah et al 2015 Bruxvoort et al 2013 Surveillance system • An adequate supply of technologically relevant surveillance tools in malaria-affected regions. • Implementation of the surveillance system for monitoring infections and progress toward elimination.…”
Section: Roles Of Diagnostic Test Surveillance and Vaccines In The Na...mentioning
confidence: 99%
“…This may, in part, be due to a lack of training for health care workers and medical laboratory professionals. In Ghana, it has been shown that providing microscopy training improved the ability of medical laboratory professionals to correctly identify malaria parasites from 64 to 87% (Tetteh et al 2021 ) - this is indicative of a great improvement in diagnostics as the result of a relatively short training program. There is also evidence from another study in Ghana that the integration of RDTs at the informal private drug retailers will result in a reduction in the prescription of antimalarials for malaria-negative individuals.…”
Section: Roles Of Diagnostic Test Surveillance and Vaccines In The Na...mentioning
confidence: 99%
“…The RDT and microscopic examinations were conducted at the community health center and then sent to the Banyumas Regency Community Health Laboratory to be cross-checked for the type of Plasmodium. Using a microscope to diagnose malaria through parasite detection is the gold standard [30], [31]. Therefore, laboratories at all levels should regularly assess skills, test, and perform quality control to ensure operability, specifically in areas with high transmission [18], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Not all analysts can properly prepare blood preparations, hence, its implementation requires more samples to cross-check microscopic examination in the laboratory. The ability, skills, and professional competence of a microscopic in making blood preparations, coloring, and checking greatly determine the discovery of malaria parasites, specifically when the density of parasites is low [30]. Therefore, the accuracy and truth of the examination by microscopic need to be observed and monitored continuously [37].…”
Section: Discussionmentioning
confidence: 99%